Leveraging an open source VPN technology to end user. - Azmat, Farok; Hamdan, Md Ikhwan; Jusoff, Kamaruzaman (Canadian Center of Science and Education, 2009)
Virtual Private Network (VPN) can be implemented by corporate and public user in a few methods. The methods included proprietary or open source solutions. It has shown great potential due to its encrypted traffic flow which gives it a secure environment. With a good reception of internet in Malaysia it is unfortunate that the major Internet Service Providers (ISPs) have imposed packet filtering. In effect they have throttled the fast broadband to become a slow medium. As a result it gives a disadvantage to active end user. To overcome an ISP packet filtering which slows down internet traffic, this paper intends to study and provide a sample of VPN solution service to end user to improve the current problem.